The new Milton criticism - Herman, Peter C., 1958-; Sauer, Elizabeth, 1964- (Cambridge University Press, 2012)
"The New Milton Criticism seeks to emphasize ambivalence and discontinuity in Milton's work and interrogate the assumptions and certainties in previous Milton scholarship. Contributors to the volume move Milton's open-ended poetics to the centre of Milton studies by showing how analysing irresolvable questions - religious, philosophical and literary critical - transforms interpretation and enriches appreciation of his work. The New Milton Criticism encourages scholars to embrace uncertainties in his writings rather than attempt to explain them away. Twelve critics from a range of countries, approaches and methodologies explore these questions in these new readings of Paradise Lost and other works. Sure to become a focus of debate and controversy in the field, this volume is a truly original contribution to early modern studies"--